Understanding the mechanisms of cooperative physico-chemical treatment and mechanical disintegration of biomass as a route for enhancing enzyme saccharification - Ibbett, Roger; Gaddipati, Sanyasi; Tucker, Gregory A. (Springer Verlag, 2017)
A novel chemico-kinetic disintegration model has been applied to study the cooperative relationship between physico-chemical treatment and supplementary wet-state milling of biomass, as an efficient process route to achieve high enzyme accessibility. Wheat straw, Miscanthus and short-rotation willow were studied as three contrasting biomass species, which were subjected to controlled hydrothermal pretreatment using a microwave reactor, followed by controlled wet-state ball-milling. Comparative particle disintegration behaviour and related enzyme digestibilities have been interpreted on the basis of model parameters and with evaluation of textural and chemical differences in tissue structures, aided by the application of specific material characterisation techniques. Supplementary milling led to a 1.3×, 1.6× and 3× enhancement in glucose saccharification yield after 24 h for straw, Miscanthus and willow, respectively, following a standardised 10-min hydrothermal treatment, with corresponding milling energy savings of 98, 97 and 91% predicted from the model, compared to the unmilled case. The results confirm the viability of pretreatment combined with supplementary wet-milling as an efficient process route. The results will be valuable in understanding the key parameters for process design and optimisation and also the key phenotypical parameters for feedstock breeding and selection for highest saccharification yield.